Pentingnya Perencanaan dalam Program Imunisasi di Dinas Kesehatan Kota Surabaya - Karlina Okta Viani (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2017)
Plannig of the health program in district level has been more dominated by top-down process. The targets specified from top level are ususally based on national projections and incompatible with the real situation in this area. The goal of this research is to analyse annual health planning in Immunization program Dinas Kesehatan Kota Surabaya. The research is a descriptive study with qualitative data. Data collected with in-depth interview to person in charge of program and document observation in City Health Department of Surabaya. The result of this research are: (1) Technical planning such as amount of target person of immunization, amount of logistic and vaccine needs, financial planning has been done, but the administrative implementation has not been fully done showed by some documents which actually do not exist. (2) Non-technical planning that is based on the problems of last year have not been implemented. (3) POA (Plan of Action) has never been made in immunization program, so it is necessary to form POA raw format and guidelines for the preparation of planning. (4) Steps in planning has not conform the rules justified. (5) Annual Training is required for the planning in immunization program for each person in charge. Keywords: district health department, immunization program, planning